Softening the blow: U.S. state-level banking deregulation and sectoral reallocation after the China trade shock - Mathias Hoffmann; Lilia Ruslanova (University of Zurich, Department of Economics, 2021)
U.S. state-level banking deregulation during the 1980's mitigated the impact of the China trade shock (CTS) on local economies (states and commuting zones) a decade later, in the 1990s. Local economies, where local banking markets opened up earlier, were also effectively financially more integrated by the 1990's and saw smaller declines in house prices, wages, and income following the CTS. We explain this pattern in a theoretical model that emphasizes the stabilizing effect of financial integration on demand for housing and on housing prices: faced with an adverse shock to their region's terms-of-trade (i.e. the CTS), households in more open states can more easily access credit to smooth consumption. This stabilizes consumer demand for housing, keeps the relative price of housing up, stabilizes wages in the non-tradable sector and thus facilitates the sectoral reallocation of labor away from import-exposed manufacturing towards the housing sector. This in turn stabilizes income and consumption. We corroborate these predictions of our model in state- and commuting zone level data. Then, using granular bank-county-level data,we show that household consumption smoothing in response to the CTS was easier in financially open areas, because geographically diversified banks were more elastic in their lending response to household's increased demand for credit. Our findings highlight that household access to finance is important to ease adjustment after asymmetric terms-of-trade shocks in monetary unions, in particular when the geographical mobility of labor is limited.
Keywords: F16; F41; G18; G21; J20; 330; Banking deregulation; China trade shock; sectoral reallocation; house prices; consumer access to finance